2021
DOI: 10.3390/cells10020479
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Cell Death Pathways during Malaria Infection: What Do We Know So Far?

Abstract: Malaria is a parasitic disease (caused by different Plasmodium species) that affects millions of people worldwide. The lack of effective malaria drugs and a vaccine contributes to this disease, continuing to cause major public health and socioeconomic problems, especially in low-income countries. Cell death is implicated in malaria immune responses by eliminating infected cells, but it can also provoke an intense inflammatory response and lead to severe malaria outcomes. The study of the pathophysiological rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(20 citation statements)
references
References 253 publications
(243 reference statements)
2
18
0
Order By: Relevance
“…Il1β transcript abundance positively correlated with parasitemia in the E6.5 infection group and multivariate modeling showed that infection at E8.5 increased placental transcription of this factor. This observation is consistent with another model of malaria infection, in which reduction of IL-1β signaling improved pregnancy outcome [ 22 ]; thus, IL-1β appears to be a universal driver of poor birth outcomes in malaria, perhaps through inflammasome assembly and/or the initiation of pyroptosis [ 55 ].…”
Section: Discussionsupporting
confidence: 86%
“…Il1β transcript abundance positively correlated with parasitemia in the E6.5 infection group and multivariate modeling showed that infection at E8.5 increased placental transcription of this factor. This observation is consistent with another model of malaria infection, in which reduction of IL-1β signaling improved pregnancy outcome [ 22 ]; thus, IL-1β appears to be a universal driver of poor birth outcomes in malaria, perhaps through inflammasome assembly and/or the initiation of pyroptosis [ 55 ].…”
Section: Discussionsupporting
confidence: 86%
“…Il1β transcript abundance positively correlated with parasitemia in the E6.5 infection group only but no changes in its expression were detected in the other infection models. This observation is noteworthy because in another model of infection during late pregnancy, reduction of IL-1β signaling improves pregnancy outcome [13]; thus, IL-1β may play a pathogenic role in our E6.5 infection model as well, perhaps through inflammasome assembly and/or the initiation of pyroptosis in gestational tissues, as has been demonstrated in other models of PM [45].…”
Section: Discussionsupporting
confidence: 59%
“…Malaria is a parasitic disease caused by the protozoa pathogens of the Plasmodium genus, which accounts for 228 million infected people globally in 2018 ( 259 ). Transmission occurs primarily through the bite of an infected female Anopheles mosquitoes, which inoculate the highly infective sporozoite forms into the mammalian host ( 260 , 261 ).…”
Section: Pyroptosis Defends Against Intracellular Protozoan Parasitesmentioning
confidence: 99%